Analisis Akar Masalah Noise pada Instrument Panel (Dashboard) Kendaraan Menggunakan Pendekatan Why-Why Analysis dan Fishbone Diagram - Sifha Awaludin; Muh Amirudin; Yudi Prastyo (Journal of Engineering and Applied Technology, 2025)
Noise issues in vehicle instrument panels remain a critical challenge in automotive interior quality, particularly in the form of rattle and squeak phenomena that affect customer perception and product reliability. This study examines the root causes of instrument panel noise through an integrated application of Why-Why Analysis and Fishbone Diagram. The research is based on an in-depth analysis of documented manufacturing practices, dimensional variability, material behavior, and assembly conditions commonly encountered in automotive production. The findings indicate that noise generation is primarily driven by inconsistent dimensional gaps resulting from process variability rather than design deficiencies alone. Why-Why Analysis reveals that inadequate fixture maintenance, inconsistent adherence to standard operating procedures, and limited sensitivity in quality control systems represent the most dominant root causes. The Fishbone Diagram further demonstrates how human factors, equipment condition, material characteristics, measurement limitations, assembly methods, and environmental conditions interact to amplify noise risks. By combining both analytical approaches, the study provides a comprehensive understanding of the mechanisms behind instrument panel noise and highlights the importance of holistic process control and continuous improvement strategies to achieve sustainable NVH performance.